2021
DOI: 10.1111/pbr.12917
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and validating SSR markers linked with rust resistance in lentil (Lens culinaris)

Abstract: Recombinant inbred lines (RILs) developed from a cross between rust resistant (FLIP‐2004‐7L) and susceptible (L‐9–12) genotypes were phenotyped against lentil rust at two hot‐spot locations for two consecutive years (2017–2018 and 2018–2019) and analysed genetically for molecular map construction. Based on the mean score of both the locations, the RILs were classified into resistant and susceptible classes. The frequency distribution of disease severity in the RILs did not show a continuous variation, which st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Resistance to rust in lentil has been identified both in cultivated lentils and its wild relatives and frequently reported to be monogenic [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 33 ] which does not exclude the existence of polygenic resistance. As for most cool season grain legumes [ 8 , 27 ], the phenotypic expression of the rust resistance reactions reported so far in lentils is poorly described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to rust in lentil has been identified both in cultivated lentils and its wild relatives and frequently reported to be monogenic [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 33 ] which does not exclude the existence of polygenic resistance. As for most cool season grain legumes [ 8 , 27 ], the phenotypic expression of the rust resistance reactions reported so far in lentils is poorly described.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to rust has been reported in lentil [ 9 , 10 , 11 ], even when the variable levels of detail hinder the comparison of results due to a lack of information details regarding the inoculation conditions, inoculum identity or the resistance components assessed. The few genetic studies available suggest monogenic control [ 12 , 13 , 14 , 15 ] that does not preclude the existence of polygenic resistance; variable levels of incomplete resistance have also been reported [ 9 , 11 ] although its inheritance is not yet studied. Stability and durability of resistance is one of the most important concerns for breeders, which reinforces the need to search and characterize additional sources of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, climate change in this region is influencing the dynamics of biotic and abiotic cues that severely impede lentil productivity. Earlier reports have revealed that collar rot, Stemphylium and Alternaria blight and rust are major biotic vagaries that decelerate lentil cultivation in this region and other South Asian countries (Kushwaha et al, 2019;Mondal et al, 2021;Roy et al, 2021;Singh et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Although, the application of genomics in lentil has fast paced recently, breeding approach still requires (i) application of available genomic resources such as QTLs, linkage maps, and association studies in lentil breeding programs as performed in other legume crops such pigeonpea and chickpea ( Roorkiwal et al, 2020 ), (ii) several QTLs have been reported in lentil related to different agronomically important traits; however, efforts toward fine mapping of those QTLs are limited, and (iii) markers related to several traits such as rust, stemphylium blight, and selenium uptake are available that could be utilized in marker-assisted breeding programs. However, the pace of development of such markers with tight linkage in very slow as compared to other legumes ( Saha et al, 2010a , b ; Ates et al, 2016 ; Dikshit et al, 2016 ; Singh et al, 2021b ). There is a need to identify tightly associated markers for other important traits that could be utilized in MAS for lentil yield improvement.…”
Section: Genomic Innovations Reveal a New Genetic Landscape For Lenti...mentioning
confidence: 99%